Aplikasi Prinsip Ekonomi Islam Dalam Menyelesaikan Persoalan Ekonomi - Rina Anggraini; Yefri Joni; Awaluddin Awaluddin; Sinky Adella (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
As a religion and a system of life, Islam has provided a solution to today's economic problems. Poverty, unemployment, scarcity and economic inequality are economic problems that never end, and even raise new problems. Instruments and principles of Islamic teachings such as Tauhi, Khilafah, Togetherness and justice are basic values ​​that will give happiness to humans in meeting their needs. The principle of monotheism teaches an attitude to always be protected from everything that will damage human life. This principle is revealed to be an integral part of the behavior of consumers, producers and distributors. Absolute Ownership or absolute ownership is Allah SWT and is realized by humans, so this value becomes a part in realizing benefit in fulfilling needs and reducing or even eliminating economic problems such as poverty, unemployment and economic inequality. This problem arises because humans feel that they have all the economic resources and are free to use them without any binding value, even though humans are only given temporary rights in controlling these resources (relative ownership). Real analysis of economic problems will be realized through awareness as a servant of God who is given the mandate to manage this nature, it will bring about sufficient simplicity. The caliphate aspect as an Islamic economic principle provides a way to solve economic problems by maximizing the function of the state as an economic control and controller in order to achieve mutual benefit. While the aspect of justice contributes to solving economic problems by providing space proportionally by always encouraging economic growth through existing economic potential and poverty protection through income distribution (zakat, infaq and shadaqah), justice will be realized together in the frame of brotherhood. Keywords: Islamic Economic Principles; Solving Economic Problem